1997
DOI: 10.1590/s0103-90161997000300018
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a long-term optimal irrigation strategy for dry beans in Parana State, Brazil

Abstract: The economical benefits of different irrigation strategies were assessed by long term simulation (20 years) for dry beans in Paraná, Brazil. The model BEANGRO was used to simulate crop yield and irrigation requirements assuming eight levels of irrigation threshold (20 to 90% of the remaining soil available water in steps of 10%), in addition to a level considering no irrigation. Net return was the objective function to select the optimum irrigation management strategy, assuming fixed and stochastic distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
10

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
1
4
0
10
Order By: Relevance
“…In addition, the RMSE was low (2.47%). These results are consistent with previous studies that showed that the model appeared to simulate the phenology of the bean cultivars adequately (FARIA et al, 1997;MEIRELES et al, 2002). …”
Section: Estimated Duration Of the Phenological Stages Of The Beansupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the RMSE was low (2.47%). These results are consistent with previous studies that showed that the model appeared to simulate the phenology of the bean cultivars adequately (FARIA et al, 1997;MEIRELES et al, 2002). …”
Section: Estimated Duration Of the Phenological Stages Of The Beansupporting
confidence: 93%
“…In Brazil, Faria et al (1997) used simulations with CROPGRO-Dry bean to evaluate different strategies for the irrigation management of beans in the State of Paraná. Meireles et al (2003) calibrated the CROPGRO-Dry bean model to quantify decreases in the yield of beans sown on 36 sowing dates in Santo Antônio de Goiás, Goiás State.…”
Section: Introductionmentioning
confidence: 99%
“…A transpiração é proporcional à energia interceptada pelo dossel da cultura e a evaporação do solo depende da quantidade de energia que atinge a superfície do solo, sendo afetadas por índice de área foliar, albedo do solo, e teor de água no solo (FARIA et al, 1997a).…”
Section: Methodsunclassified
“…Dentre os estudos já realizados utilizando-se o CROPGRO-Dry Bean, destacam-se: avaliação de diferentes estratégias de manejo de irrigação visando ao melhor benefício econômico para a cultura do feijoeiro no Estado do Paraná (FARIA et al, 1997a); calibração do modelo BEANGRO para o feijoeiro nas condições de Londrina, PR, com intuito de testar sua performance em simular a fenologia, produção de matéria seca e grãos desta cultura sob diferentes condições ambientais (FARIA et al, 1997b); determinação das épo-cas de semeadura com menores riscos para a cultura do feijoeiro, em condições de sequeiro e irrigada, em Santo Antônio de Goiás (GO), utilizando as produtividades potencial e real, e a quebra relativa de produtividade simulada pelo CROPGRO-Dry Bean (MEIRELES, 2000e MEIRELES et al, 2001; determinação da necessidade de irrigação pela cultura do feijoeiro no nordeste da Bacia do Rio Tibagi, no Estado do Paraná, utilizando-se o CROPGRO-Dry Bean associado a um sistema de informações geográficas para regionalizar as informações (HEINEMANN e HOOGENBOOM, 2001). …”
Section: Introductionunclassified
“…For the dry bean, for instance, Faria et al (1997b) calibrated the BEANGRO model for the conditions of Londrina, PR -Brazil, testing its performance under several environmental conditions. Although some modifications were necessary, results indicated that the model is adequate to estimate phenology and grain yield for two cultivars for several sowing dates and moisture regimes, allowing its use for climatic risk and technical and economical viability studies of this crop under arid and irrigated conditions.…”
Section: Introductionmentioning
confidence: 99%